Answer:
5:4
Step-by-step explanation
If your shoes to flip-flops are 10:8 then the starting ratio will be 10:8 but 10 and 8 are both divisible to 2 so you can simplify 10:8 to 5:4
Y is the answer for four right angles
Ok so this question:
y + 1 = - ( x - 2 ) (distribute the negative inside the parenthesis)
y + 1 = -x + 2 (substitute the y= -1)
-1 + 1 = -x + 2
0 = -x + 2 (take two to the other side)
-2 = -x (divide the negative away from x)
2 = x
Answer: ![4y^{2}(2x-9y)^{2}](https://tex.z-dn.net/?f=4y%5E%7B2%7D%282x-9y%29%5E%7B2%7D)
Step-by-step explanation:
We have the following polynomial:
![(4xy-18y^{2})^{2}](https://tex.z-dn.net/?f=%284xy-18y%5E%7B2%7D%29%5E%7B2%7D)
This is a polynomial of the form
. Following this rule to expand it, we have:
![(4xy)^{2}-2(4xy)(18y^{2})+(18y^{2})^{2}](https://tex.z-dn.net/?f=%284xy%29%5E%7B2%7D-2%284xy%29%2818y%5E%7B2%7D%29%2B%2818y%5E%7B2%7D%29%5E%7B2%7D)
![16x^{2}y^{2}-144xy^{3}+324y^{4}](https://tex.z-dn.net/?f=16x%5E%7B2%7Dy%5E%7B2%7D-144xy%5E%7B3%7D%2B324y%5E%7B4%7D)
Applying common factor
:
![4y^{2}(4x^{2}-36xy+81y^{2})](https://tex.z-dn.net/?f=4y%5E%7B2%7D%284x%5E%7B2%7D-36xy%2B81y%5E%7B2%7D%29)
Note the polynomial inside the parenthesis is a perfect square trinomial, which can be factored to
. Hence, the final simplification is:
![4y^{2}(2x-9y)^{2}](https://tex.z-dn.net/?f=4y%5E%7B2%7D%282x-9y%29%5E%7B2%7D)